Choir Learning Through Online Demonstration Method For Students Of SMK Negeri 2 Kasihan Bantul Yogyakarta (Jurnal Seni Musik, 2022)
During the Covid-19 pandemic, the choral learning at SMK Negeri 2 Kasihan, which was initially carried out with face-to-face learning using the drill and demonstration method, was shifted to online learning using the demonstration method. This research was conducted to find out, analyze and describe the implementation of online choir learning with the demonstration method at SMK Negeri 2 Kasihan. This study used a qualitative descriptive research method with a pedagogical approach. The sources of research data were obtained from the stages of observation, interviews, and documentation. The data analysis techniques used are data reduction techniques (data reduction), data presentation (data display), and data verification or drawing conclusions. The data validity technique used is technical triangulation, source triangulation, and time triangulation. The location of research was carried out at SMK Negeri 2 Kasihan in Bantul located at Jl. PG. Madukismo, Jomegatan, Ngestiharjo, Kasihan Sub-District, Bantul Regency, Special Region of Yogyakarta (DIY). The results show that the process of implementing choir learning was carried out using 3 (three) learning applications, namely the Google Classroom application as a medium for delivering material in the form of theory, Google Meet and Zoom Meeting as a medium for remote meetings via video conference.